Layered composite and method for producing same - Patents.com
Patent Information
- Application Number
- JP2024552509
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-04
- Filing Date
- 2023-03-02
- Publication Date
- 2025-03-13
AI Technical Summary
【0014】 層状複合体の熱容量も、前述の典型的な熱可塑性ホットメルト接着フィルムと比較して著しく増加させることができる。また、ポリマー層のより少ない重量により燃焼挙動にも好影響を与えることができる。さらに、本発明による方法は、複合体の水分感受性(moisture sensitivity)が、EVA、PVB、またはイオノマー中間層と比較して低減するという利点を有する。加えて、複合ガラスの場合、製造時間は数時間から数分に短縮することができる。また、複合体の製造は室温またはわずかに高い温度で行うことができ、したがってオートクレーブ(autoclaving)プロセスが不要となるので、エネルギー消費も削減される。
Smart Images

Figure 2025507038000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a layered composite that includes a substrate, a cover layer, and a polymeric layer disposed therebetween, the polymeric layer being bonded to the substrate and the cover layer by an adhesive layer. [Background technology]
[0002] Currently, composite safety glass made of two rigid glass layers laminated together is typically adhesively bonded by a hot-laminable polyvinyl butyral (PVB) or ethylene vinyl acetate copolymer (EVA) film. Thus, for example, EP 3438206 A1 describes a laminate comprising a thermoplastic film and a glass sheet. Special products with ionoplast interlayers are sold, in particular under the trade name SentryGlas. Such ionoplast interlayers are specified to be more durable and rigid than PVB interlayers.
[0003] EP 2986451 discloses a method for forming a composite glass structure, the method comprising the steps of: introducing a continuous strip of flexible glass substrate having a thickness of 0.3 mm or less to a non-glass substrate material, the non-glass substrate material having a coefficient of thermal expansion (CTE) greater than that of the flexible glass substrate; laminating the flexible glass substrate to the non-glass substrate material at an elevated temperature; and controlled cooling of the composite glass structure to introduce a compressive stress across the thickness of the flexible glass substrate, the flexible glass substrate having a compressive strength of at least 40 MPa across the thickness of the flexible glass substrate.
[0004] US Patent Application Publication No. 2003 / 0124296 relates to a thermoplastic polymer film having a haze of at least 4%, the film being suitable as a laminate barrier to prevent objects from penetrating the laminate with sufficient force upon impact to shatter glass, the laminate including at least one glass layer and a thermoplastic polymer film self-adhesively attached directly to the glass layer, the thermoplastic polymer film consisting essentially of an ionomeric polymer and a UV light absorber, the laminate being capable of withstanding repeated or longer loads without fracture, even after the glass has fractured.
[0005] U.S. Pat. No. 5,352,528 discloses a composite pane having at least one glass pane and at least one film made of a plastic including PVC having transparency resistant to aging and weathering and energy absorption suitable for a safety pane, an adhesive film is disposed between the glass pane and the plastic film, the adhesive film having stronger adhesion to the glass than the plastic film, and the adhesive film includes a terpolymer including ethylene, vinyl acetate or acrylic acid ester, and maleic anhydride.
[0006] DE 10 2018 124 601 A1 describes a glass structure for glazing or glass support of handrails and / or rails with a composite element formed as a glass laminate consisting of at least two glass panes connected by a plastic adhesive interlayer, at least one end of the composite element having an edge protector that is connected in at least some areas to the respective end faces of at least two glass panes of the glass laminate such that the interlayer is protected against the effects of moisture. Reference is here also made to WO 2020 / 069983 A1.
[0007] WO 2014 / 086610 relates to a laminate made of two rigid substrates and an adhesive film arranged therebetween, at least one of the rigid substrates being transparent, the adhesive film having a thickness of 80 μm or less, the adhesive film comprising at least one adhesive layer made of an adhesive compound to which one or more softeners have been added, at least one of which is a reactive softener, the proportion of the softeners in the adhesive compound being at least 15 wt % in total, and the proportion of the reactive softener in the adhesive compound being at least 5 wt %.
[0008] WO 2020 / 064297 discloses a composite glass pane and a method for producing it. The composite glass pane has two glass or polycarbonate panes and at least one polymer film or film laminate adhesively bonded therebetween and an electronic function unit arranged therebetween. A cutout of the polymer film or film laminate is provided in a partial surface area of the composite glass pane, and a completely pre-finished electronic function module is accommodated in the cutout, which has a thickness at most equal to the thickness of the polymer film or film laminate. The electronic function module has the shape of a flat prism, in particular a flat rectangular parallelepiped, or a flat circular disk, and the two main faces of the flat prism or the flat circular disk are coated with an adhesive for adhesively bonding the electronic function module between the glass or polycarbonate panes.
[0009] WO 2015 / 097111 describes a method for producing a layered composite, the layered composite comprising a substrate, a cover layer, and an adhesive layer disposed between the substrate and the cover layer. The adhesive layer is at least partially in contact with the substrate and the cover layer. The method comprises the steps of: pivoting the substrate and the cover layer relative to each other, so that the distance from the upper cover layer end to the upper substrate end is reduced and the adhesive is moved in the direction of the upper substrate end and the upper cover layer end. This is performed such that during at least a part of step B), the angle bisector (1000) of the angle α is at an angle of more than -45° and less than 45° with respect to the vertical.
[0010] German Utility Model No. 202013105933 discloses a layered composite comprising a substrate, a cover layer and a curable adhesive layer arranged between the substrate and the cover layer, the adhesive layer being in at least partial contact with the substrate and the cover layer. The substrate comprises a mineral material, the cover layer comprises glass, an electrical functional unit is arranged between the substrate and the cover layer, and in the layered composite an average content of air bubbles encapsulated in the adhesive layer having a maximum dimension of 100 μm or more is 100 air bubbles / m 2 is less than. Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has the object of providing an improved layered composite which can be used, for example, as multi-pane safety composite glazing, and a method for producing it as nearly bubble-free as possible. [Means for solving the problem]
[0012] This object is achieved according to the invention by a layered composite according to claim 1 and a method according to claim 9. Advantageous refinements are specified in the dependent claims, which can be combined with one another in any way, unless a contrary result clearly follows from the context.
[0013] The layered composite according to the invention has the advantage that significantly higher composite strengths can be achieved without increasing the weight of the composite, in particular the combined compressive strength and puncture strength, and when an equivalent strength is required, the composite can be achieved with a lower total weight.
[0014] The heat capacity of the layered composite can also be significantly increased compared to the aforementioned typical thermoplastic hot melt adhesive films. The lower weight of the polymer layer can also have a positive effect on the fire behavior. Furthermore, the method according to the invention has the advantage that the moisture sensitivity of the composite is reduced compared to EVA, PVB or ionomeric interlayers. In addition, the production time can be reduced from hours to minutes in the case of composite glass. Also, energy consumption is reduced, since the production of the composite can be carried out at room temperature or slightly elevated temperatures, thus eliminating the need for an autoclaving process.
[0015] The invention is explained in more detail by the following figures, without however being limited thereto. [Brief description of the drawings]
[0016] [Figure 1] 1 shows a layered composite according to the present invention. [Diagram 2] 3 shows a further layered composite according to the present invention. [Diagram 3] 3 shows a further layered composite according to the present invention. [Figure 4] 1 shows a layout of a method for producing a layered composite according to the present invention. [Diagram 5] 1 shows a layout of a method for producing a layered composite according to the present invention. [Figure 6] 1 shows a layout of a method for producing a layered composite according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] 1 shows a layered composite comprising a substrate 10, a cover layer 40 and a polymer layer 30 arranged therebetween, the polymer layer being bonded to the substrate 10 and to the cover layer 40 by adhesive layers 20, 21. According to the invention it is provided that the cover layer 40 has a light transmission according to DIN EN ISO 410 of 50% or more, the polymer layer 30 has a tensile strength according to DIN EN ISO 527 of 30 MPa or more and the adhesive layers 20, 21 are layers of a cured, e.g. multi-component reactive adhesive and / or radiation-curable adhesive.
[0018] Examples of suitable materials for the substrate 10 are mineral materials or glass. Suitable mineral materials are, for example, rocks, natural stone, concrete, gypsum, etc. "Natural stone" is understood quite generally as all stones found in nature. Preferred natural stones are granite, marble, quartz, quartz composite, travertine, sandstone, slate, and agate. Examples of suitable glasses are E glass, S glass, M glass, quartz glass, borosilicate glass, crown glass, soda-lime glass, float glass, flint glass, and / or lead crystal glass. The glass of the substrate 10 may be colored or uncolored. The thickness of the substrate 10 is preferably 1 mm or more and 40 mm or less, more preferably 2 mm or more and 20 mm or less.
[0019] Examples of suitable materials for the cover layer 40 are polymethyl(meth)acrylate, polycarbonate, and glass. Examples of suitable glasses are E-glass, S-glass, M-glass, quartz glass, borosilicate glass, crown glass, soda-lime glass, float glass, flint glass, and / or lead crystal glass. The glass of the cover layer 40 may be colored or uncolored. The thickness of the cover layer 40 is preferably 1 mm or more and 40 mm or less, more preferably 2 mm or more and 20 mm or less.
[0020] The cover layer 40 may be characterized as having a light transmission according to DIN EN ISO 410 of 50% or more and therefore being at least partially transparent. The light transmission is preferably 60% or more, more preferably 70% or more, particularly preferably 80% or more, very particularly preferably 90% or more. According to an embodiment, the substrate 10 may also have the above-mentioned light transmission (50% or more, preferably 60% or more, more preferably 70% or more, particularly preferably 80% or more, very particularly preferably 90% or more). According to a further embodiment, the polymer layer 30 may also have the above-mentioned light transmission. According to a further embodiment, the adhesive layers 20, 21 may also have the above-mentioned light transmission. According to a further embodiment, the layer composite as a whole has the above-mentioned light transmission. In particular, the light transmission of the layer composite may be 90% or more.
[0021] The polymer layer 30 may be embodied as continuous or discontinuous. The area of the polymer layer defined by its outer edge is preferably equal to or greater than the area of the substrate 10 and / or the cover layer 40. For example, after fabrication of the layered composite, the edges can be trimmed so that the areas of the substrate 10, polymer layer 30, and cover layer 40 are equal.
[0022] The polymer layer 30 has a tensile strength according to DIN EN ISO 527 of 30 MPa or more. The tensile strength is preferably 40 MPa or more and 300 MPa or less, more preferably 50 MPa or more and 250 MPa or less. For the purposes of the present invention, it is assumed that the tensile strength of the polymer layer 30 in the layered composite can be made equal to the tensile strength of a free layer of the same material. Therefore, to select a suitable polymer layer 30 according to the present invention, reference can be made, for example, to the data sheet of the polymer film. If the tensile strength of the polymer layer is different in the machine direction and the transverse direction, the lower of the two values is selected.
[0023] The thickness of the polymer layer 30 may be 0.05 mm to 4 mm, preferably 0.10 mm to 3 mm, more preferably 0.15 mm to 2 mm. The polymer layer 30 may be formed in one part or in multiple parts. A multiple part polymer layer may be realized, inter alia, by laminated film stacks.
[0024] Adhesive layer 20 is an adhesive layer that bonds substrate 10 to polymer layer 30. Adhesive layer 21 bonds cover layer 40 to polymer layer 30. It is preferred that the same adhesive is present in adhesive layers 20 and 21. The thickness of adhesive layer 20 and / or 21 can be 1 μm or more and 650 μm or less (preferably 2 μm or more and 400 μm or less, more preferably 3 μm or more and 150 μm or less, and particularly preferably 5 μm or more and 50 μm or less).
[0025] The adhesive layers 20, 21 are layers of curable reactive adhesives and / or radiation curable adhesives. The adhesives are preferably transparent, in particular two-component adhesives such as epoxy resins, (meth)acrylate resins, and polyurethane resins, and radiation curable adhesives such as (meth)acrylates and urethane (meth)acrylates. Dual cure adhesives, which undergo simultaneous or successive radiation and non-irradiation curing, are also suitable.
[0026] In the layered composite according to the invention, the average content of air bubbles enclosed in the adhesive layers 20, 21 having a maximum dimension of 100 μm or more is preferably 100 air bubbles / m 2 The bubble content can be determined, for example, by optical evaluation and counting of the bubbles. An automated method is also conceivable, where the layered composite is inspected by means of a camera and software for image processing. The average content of these bubbles is preferably less than 10 bubbles / m 2 less than 1 bubble / m 2 The lower the air bubble content, the higher the quality of the layered composite is perceived by the end user.
[0027] According to further embodiments, the layered composite may include multiple polymer layers 30. For example, the layered composite may have the following structure, where the individual layers are described for simplicity based on their reference numbers in FIG. 1: 10-[20-30] n -21-40, where [20-30] n refers to the repeating unit comprised of adhesive layer 20 and polymer layer 30, and n refers to the number of repeating units. For example, n can have a value of 2, 3, 4, 5, 6, 7, 8, 9, or 10.
[0028] According to one embodiment, the cured adhesive of the adhesive layer (20, 21) has an elongation at break according to DIN EN ISO 527 of 10% or more. The elongation at break is preferably 10% to 600%, more preferably 50% to 500%, particularly preferably 200% to 460%. Without being bound by theory, it is hypothesized that with such an elongation at break, an optimization of two opposing effects can be achieved: an adhesive layer that is too elongated is undesirable from the standpoint of heat resistance, while a layer that is not sufficiently elongated worsens the fixation of the bonded glass fragments.
[0029] According to a further embodiment, the cured adhesive of the adhesive layers 20, 21 has a tensile strength according to DIN EN ISO 1465 of ≧2 MPa. The tensile strength value is preferably ≧4 MPa and ≦50 MPa, more preferably ≧6 MPa and ≦35 MPa.
[0030] It is particularly preferred if the cured adhesive of adhesive layers 20, 21 simultaneously has the break elongation and tensile strength described.
[0031] According to a further embodiment, the polymer layer 30 comprises a polyester polymer, a thermoplastic polyurethane polymer or a polycarbonate polymer. The polymer layer 30 preferably comprises a stretched, particularly preferably a biaxially stretched polyester film. Such a polyester film may have a softening temperature of 200° C. or more. In this way, the thermal stability of the layered composite in the event of fire is improved, in particular in comparison with EVA and PVB composite glass. Biaxially stretched polyester films may reach tensile strengths of 150 MPa or more. Such high tensile strengths have an advantageous effect on the mechanical stability of the layered composite, in particular in situations such as storms during which debris is blown into the air.
[0032] According to further embodiments, the polymer layer 30 is formed as a film without depressions, as a film with one or more depressions 31, as a woven fabric, or as a nonwoven fabric. The case where the polymer layer 30 is formed as a film without depressions can be seen in FIG. 1. FIG. 2 shows the case where the polymer layer 30 is formed as a film with depressions 31. The depressions 31 form a more continuous adhesive bond between the substrate 10 and the cover layer 40. This can result in increased strength and special optical effects. If the adhesive and the polymer layer have the same refractive index, the depressions will not be visible.
[0033] The depressions 31 may be arranged regularly or randomly. Examples of the cross-section of the depressions 31 are circular, elliptical, square, rectangular, and strip-shaped. The depressions 31 may occupy, for example, 1% to 70%, more preferably 5% to 50%, of the total area of the film forming the polymer layer 30. A continuous adhesive bond between the substrate 10 and the cover layer 40 can also be realized by designing it as a woven or nonwoven fabric.
[0034] According to a further embodiment, at least a portion of the polymer layer 30 protrudes from the layered composite, as shown in Figure 3. For example, the polymer layer 30 may protrude 0.5 cm to 20 cm, more preferably 1 cm to 10 cm.
[0035] The protrusions of the polymer layer 30 may be used to attach and / or seal the layered composite to a frame, for example a window frame. This has the advantage in the case of windows of increased compressive strength, for example in the case of extreme wind loads.
[0036] According to a further embodiment, the polymer layer 30 may not or is not post cross-linked. Thus, in particular ionomeric films are excluded. Post cross-linking in particular relates to thermal post cross-linking, but also includes photochemical post cross-linking.
[0037] According to further embodiments, the layered composite has the following characteristics: the substrate 10 and the cover layer 40 are each independently a glass layer having a thickness of 1 mm or more and 40 mm or less; the polymer layer 30 has a thickness of 0.05 mm or more and 4 mm or less (preferably 0.1 mm or more and 2 mm or less, more preferably 0.15 mm or more and 1 mm or less); - the total thickness of the polymer layer 30 and the adhesive layer (20, 21) is 0.06 mm or more and 5.3 mm or less (preferably 0.1 mm or more and 2.1 mm or less); and The thickness of the adhesive layer (20, 21) is 1 μm or more and 650 μm or less (preferably 2 μm or more and 400 μm or less, more preferably 3 μm or more and 150 μm or less, and particularly preferably 5 μm or more and 50 μm or less). The present invention has at least one of the following:
[0038] The method according to the invention will now be described with reference to Figures 4 to 6. The method for producing a layered composite according to the invention comprises: A) providing an arrangement comprising a substrate 100 and a cover layer 200, A substrate 100 includes a first substrate side 110 having a vertically upper substrate edge 120, a vertically lower substrate edge 130, a first substrate lateral edge 140, and a second substrate lateral edge 150 opposite the first substrate lateral edge; a cover layer 200 including a first cover layer side 210 having a vertically upper cover layer end 220, a vertically lower cover layer end 230, a first cover layer lateral end 240, and a second cover layer lateral end 250 opposite the first cover layer lateral end; The first substrate side 110 and the first cover layer side 210 in this arrangement face each other at an angle α, forming an angle bisector 1000 of the angle α; The upper substrate edge 120 and the upper cover layer edge 220 face each other in this arrangement; The lower substrate edge 130 and the lower cover layer edge 230 face each other in this arrangement; The first substrate lateral end 140 and the first cover layer lateral end 240 face each other in this arrangement; The second substrate lateral end 150 and the second cover layer lateral end 250 face each other in this arrangement; In this arrangement, the distance from the upper substrate edge 120 to the upper cover layer edge 220 is greater than the distance from the lower substrate edge 130 to the lower cover layer edge 230; In this arrangement, a first seal 500 is provided between the lower substrate end 130 and the lower cover layer end 230 to prevent leakage of fluid between the lower substrate end 130 and the lower cover layer end 230; In this arrangement, a second seal 510 is provided between the first substrate lateral end 140 and the first cover layer lateral end 240, thereby preventing leakage of fluid between the first substrate lateral end 140 and the first cover layer lateral end 240; In this arrangement, a third seal 520 is provided between the second substrate lateral end 150 and the second cover layer lateral end 250, thereby preventing leakage of fluid between the second substrate lateral end 150 and the second cover layer lateral end 250; This arrangement then forms an open-sided container for receiving a fluid, and further includes a hardenable adhesive 310 within the container. B) pivoting the substrate 100 and the cover layer 200 relative to one another such that the distance from the upper substrate edge 120 to the upper cover layer edge 220 decreases and the adhesive 310 moves in the direction of the upper substrate edge 120 and the upper cover layer edge 220; C) Curing the adhesive 310 Includes.
[0039] In the arrangement according to A), a polymer layer 400 having a tensile strength according to DIN EN ISO 527 of 30 MPa or more is furthermore arranged between the substrate 100 and the cover layer 200. The tensile strength is preferably 40 MPa or more and 300 MPa or less, more preferably 50 MPa or more and 250 MPa or less.
[0040] Details regarding the materials and dimensions of the substrate, cover layer, adhesive, and polymer layers have already been described in relation to the layered composite according to the invention and will not be repeated at this point. These specifications apply equally to the method according to the invention.
[0041] According to one embodiment of the method, at least during steps A), B) and C), the temperature of the polymer layer (400) is below 50° C. The temperature is preferably below 40° C., more preferably below 30° C. Thus, it is shown that an autoclave process, as is necessary for thermal crosslinking of EVA or ionomer films, does not have to be part of the method.
[0042] According to a further embodiment of the method, no heating of the layered composite to a temperature above 100° C. is carried out after step C). Preferably, heating is not carried out above 80° C., particularly preferably heating is not carried out above 60° C. It is thus shown that an autoclave process, as is necessary for thermal crosslinking of EVA or ionomer films, does not have to be part of the method.
[0043] According to a further embodiment of the method, at least at the beginning of the pivoting in step B), the adhesive 310 has a viscosity at 20° C. according to DIN EN 12092 of ≦50 000 mPas. The viscosity is preferably ≧10 mPas to ≦20 000 mPas, more preferably ≧50 mPas to ≦10 000 mPas.
[0044] According to a further embodiment of the method, the polymer layer 400 comprises a polyester polymer, a thermoplastic polyurethane polymer, or a polycarbonate polymer.
[0045] According to further embodiments of the method, the polymer layer 400 is formed as a film without recesses, as a film with one or more recesses 31 (see FIG. 2), as a woven fabric, or as a nonwoven fabric.
[0046] According to a further embodiment of the method, the polymer layer 400 may not or is not post-crosslinked. Thus, in particular ionomeric films are excluded. Post-crosslinking in particular relates to thermal post-crosslinking, but also includes photochemical post-crosslinking.
[0047] Figure 4 shows an arrangement for use in the method according to the invention, on the basis of which some spatial relationships and geometric definitions are explained, however, in Figure 4, for the sake of greater clarity, the adhesive and polymer layers present in this arrangement are not shown.
[0048] As already mentioned, in the method according to the invention, an arrangement of a substrate and a cover layer is provided. The manner in which this arrangement is constructed, such as the individual steps and their order, is not defined here.
[0049] In the arrangement as shown in Figure 4, there is a substrate 100 and a cover layer 200. The substrate has a first substrate side 110. This first substrate side 110 is adhesively bonded to a corresponding first cover layer side 210 of the cover layer 200 in a further process.
[0050] The relevant substrate or cover layer sides have various edges defined. A first substrate side 110 has an upper substrate edge 120 in a vertical (against gravity) view and an opposing lower substrate edge 130 in a vertical view. In the case shown in FIG. 4, these edges extend horizontally. Vertically extending substrate side edges 140, 150 are now positioned adjacent the upper substrate edge 120 and the lower substrate edge 130.
[0051] Also, the first cover layer side 210 has an upper cover layer end 220, a lower cover layer end 230, and two cover layer lateral ends 240, 250 facing each other. The first substrate side 110 and the first cover layer side 210 face each other, so that the substrate 200 and the cover layer 210 generally represent a "V" shaped formation. The upper substrate end 120 and the upper cover layer end 220, as well as the lower substrate end 130 and the lower cover layer end 230, face each other. Similarly, the first substrate lateral end 140 and the first cover layer lateral end 240, as well as the second substrate lateral end 150 and the second cover layer lateral end 250, face each other. In accordance with the description of the formation as "V-shaped", the distance from the upper cover layer end 220 to the upper substrate end 120 is greater than the distance from the lower cover layer end 230 to the lower substrate end 130.
[0052] The formation of the "V" creates an open-topped container, or visually a trough, through the use of sealants that seal the gap between the opposing edges of the substrate 100 and the cover layer 200.
[0053] Here, the second seal 510 seals between the first substrate lateral edge 140 and the first cover layer lateral edge 240, and the third seal 520 seals between the second substrate lateral edge 150 and the second cover layer lateral edge. The fact that the arrangement in the method according to the invention is embodied as open on one side, in particular "open on the top", means that the displaced adhesive has enough space to exit the gap formed between the substrate 100 and the cover layer 200. The fact that it is open on one side also includes that the arrangement is all around, but that the adhesive can leak out as mentioned above.
[0054] Figure 5 shows the arrangement of figure 4 in a perspective view from below. The substrate 100 and the cover layer 200, the lateral edges 140, 150, 240 and 250, as well as one of the lateral seals 520 are again visible. The first seal 500, the second seal 510 and the third seal 520 are also visible here, preventing leakage of fluids (particularly adhesive) between the lower edge of the substrate and the cover layer. The first seal 500, the second seal 510 and the third seal 520 are designed, for example, by overlapping, so that the arrangement as a whole represents an open container on the top, capable of receiving adhesive. However, they can also be combined and, for example, can exist as one seal piece as a whole.
[0055] Figure 6 shows a cross-sectional view of the arrangement shown in Figures 4 and 5, where the curable adhesive 310 and the polymer layer 400 are further present in the open-top container to be formed. The adhesive is therefore already at least partially in contact with the first substrate side 110 and the first cover layer side 210. The polymer layer 400 can be introduced before the adhesive is poured into the arrangement according to Figures 4 and 5. It is also possible to pour the adhesive first and then introduce the polymer layer into the arrangement.
[0056] The adhesive is prevented from leaking out of the container by the provided seal. Due to the cross-sectional view, the seal 520 of Figs. 4 and 5 is not shown in Fig. 6. Also, it is not important for the method according to the invention whether the adhesive 310 is poured into a completely constructed "trough" composed of the substrate 100, the cover layer 200 and the seals 500, 510, 520, or whether it is for example already present on the substrate and / or the cover layer and the "trough" is subsequently constructed. An angle α is formed between the first substrate side 110 and the first cover layer side 210. The angle bisector 1000 can be constructed accordingly.
[0057] In the method according to the invention, the substrate 100 and the cover layer are pivoted relative to each other. In this case, the distance from at least the upper cover layer end 220 to the upper substrate end 120 is increased. Visually, this can be likened to folding a book closed. In this case, the "spine" is formed by the lower end 130, 230 and the lower first seal 500. The pivoting is represented by the two curved arrows in FIG. 6. Pivoting the substrate 100 and the cover layer 200 relative to each other results in the adhesive disposed therebetween being pushed further along the gap between the substrate 100, the polymer layer 400, and the cover layer 200. Thus, the adhesive also moves further in the direction of the upper substrate end 120 and the upper cover layer end 120.
[0058] In the method according to the invention, it may be provided that during at least a part of step B (pivoting), the bisector 1000 of the angle α takes an angle of more than -45° and less than 45° with respect to the vertical. In this way, the opening of the arrangement always faces upwards, so that air bubbles trapped in the adhesive can also rise to the upper side and escape from the gap between the substrate 100 and the cover layer 200. In this case, the bisector 1000 of the angle α preferably takes an angle of more than -30° and less than 30°, more preferably more than -15° and less than 15° with respect to the vertical. This may then be referred to as an "upright adhesive bond" of the substrate 100 and the cover layer 200.
[0059] In FIG. 6, the angle bisector 1000 has an angle of 0° with respect to the vertical. In this case, a negative angle means that the angle bisector 1000 is tilted to the left, and a positive angle represents a tilt in the opposite direction. The sign of the tilt angle is also a range that depends on the observation point of view. The lower substrate edge 130 and the lower cover layer edge 230 do not necessarily have to be in contact. Because of the presence of the first seal 500, they can also be spaced apart from each other. Their spacing can be selected taking into account the desired thickness of the adhesive layer in the finished layered composite.
[0060] The adhesive 310 may be cured, for example, by UV exposure or by having a two-part adhesive reaction. EXAMPLES
[0061] The present invention is further illustrated by the following non-limiting examples.
[0062] The tensile strength (DIN EN ISO 527) of the films used was as follows:
[0063] [Table 1]
[0064] The adhesives used are listed here below: The specified elongation at break (DIN EN ISO 527) refers to the curable adhesive.
[0065] [Table 2]
[0066] All tests were performed using round transparent float glass disks (2 mm thickness / 10 cm diameter) and / or films (different thicknesses, 10 cm diameter). The adhesive bonds on the glass disks were produced using a UV-curable adhesive (adhesive layer thickness approx. 0.005 mm). Curing was performed using a 2000 W Honle UVA lamp (UVA spot 200) at a distance of 75 cm for 20 minutes, with an intensity of 50 mW / cm 2 This corresponds to a UV irradiance of
[0067] To determine the compressive and perforation strength, the samples were clamped in a steel cylinder with an outer diameter of 10 cm and an inner diameter of 8.4 mm. A spindle press with a rounded Teflon head (2 cm diameter) was used to press the samples and measure the load exerted by the Teflon head on the sample. The descent speed of the Teflon head was 15 cm / min. The compressive strength value was read when the sample body broke or split as a whole. The perforation strength value was read as soon as the stamp penetrated the sample body.
[0068] For samples up to about 1 mm thick, it was observed that the puncture strength behaved essentially linearly as a function of layer thickness during the test method, which made it possible to convert the puncture strengths of the films and adhesive layers to unit thickness (here 0.25 mm) in order to make the results more comparable.
[0069] 1. Test results for glass disks with no film between them
[0070] [Table 3]
[0071] In experiments using glass disks bonded using UV adhesive 4, the glass disks were observed to break into numerous individual pieces. In parallel experiments using UV adhesive 3, such free individual pieces occurred only to a negligible extent.
[0072] 2. Test results for curable adhesive film and polymer film (each standardized to a thickness of 0.25 mm)
[0073] [Table 4]
[0074] 3. Test results on layered composite. The layered composite had the following structure: glass / curable UV adhesive 3 / polymer film / curable UV adhesive 3 / glass.
[0075] [Table 5]
[0076] 4. Test results on a layered composite with the following structure: Glass / Curable UV Adhesive 4 / Biaxially oriented polyester film / Curable UV Adhesive 4 / Glass
[0077] The experimental setup corresponded to the compressive strength and puncture strength tests described above. In the experiment with the layered composite adhesively bonded using UV adhesive 4, it was observed that the glass disk broke into a large number of free individual pieces. In the parallel experiment with UV adhesive 3, such free individual pieces occurred only to a negligible extent.
Claims
1. A layered composite comprising a substrate (10), a cover layer (40) and a polymer layer (30) disposed therebetween, said polymer layer being bonded to said substrate (10) and said cover layer (40) by adhesive layers (20, 21); said cover layer (40) having a light transmission according to DIN EN ISO 410 of 50% or more; said polymer layer (30) having a tensile strength according to DIN EN ISO 527 of 30 MPa or more; A layered composite, characterized in that said adhesive layers (20, 21) are layers of curable reactive adhesives and / or radiation curable adhesives.
2. 2. The layered composite according to claim 1, wherein the cured adhesive of the adhesive layers (20, 21) has an elongation at break according to DIN EN ISO 527 of 10% or more.
3. 3. A layered composite according to claim 1 or 2, wherein the cured adhesive of the adhesive layers (20, 21) has a tensile strength according to DIN EN ISO 1465 of ≧2 MPa.
4. The layered composite of any one of claims 1 to 3, wherein the polymer layer (30) comprises a polyester polymer, a thermoplastic polyurethane polymer, or a polycarbonate polymer.
5. 5. The layered composite of claim 1, wherein the polymer layer (30) is formed as a film without depressions, as a film with one or more depressions (31), as a woven fabric, or as a nonwoven fabric.
6. The layered composite of any one of claims 1 to 5, wherein at least a portion of the polymer layer (30) protrudes from the layered composite.
7. The layered composite of any one of claims 1 to 6, wherein the polymer layer (30) may not be or is not post-crosslinked.
8. A layered composite having at least one of the following characteristics: the substrate (10) and the cover layer (40) are, independently of each other, glass layers with a thickness of ≧1 mm and ≦40 mm; the polymer layer (30) has a thickness of 0.05 mm or more and 4 mm or less; the sum of the thicknesses of the polymer layer (30) and the adhesive layer (20, 21) is greater than or equal to 0.06 mm and less than or equal to 5.3 mm; and the thickness of the adhesive layer (20, 21) is between 1 μm and 650 μm; The layered composite according to any one of claims 1 to 7,
9. A method for producing the layered composite of any one of claims 1 to 8, comprising the steps of: A) providing an arrangement comprising a substrate (100) and a cover layer (200), The substrate (100) includes a first substrate side (110) having a vertically-viewed upper substrate end (120), a vertically-viewed lower substrate end (130), a first substrate lateral end (140), and a second substrate lateral end (150) opposite the first substrate lateral end; The cover layer (200) includes a first cover layer side (210) having a vertically viewed upper cover layer end (220), a vertically viewed lower cover layer end (230), a first cover layer lateral end (240), and a second cover layer lateral end (250) opposite the first cover layer lateral end; The first substrate side (110) and the first cover layer side (210) in the above arrangement face each other at an angle α, and an angle bisector (1000) of the angle α is formed; the upper substrate end (120) and the upper cover layer end (220) are opposed to each other in the arrangement; the lower substrate end (130) and the lower cover layer end (230) are opposed to each other in the arrangement; the first substrate lateral end (140) and the first cover layer lateral end (240) are opposed to each other in the arrangement; the second substrate lateral end (150) and the second cover layer lateral end (250) are opposed to each other in the arrangement; In the arrangement, the distance from the upper substrate end (120) to the upper cover layer end (220) is greater than the distance from the lower substrate end (130) to the lower cover layer end (230); In said arrangement, a first seal (500) is provided between said lower substrate end (130) and said lower cover layer end (230), thereby preventing leakage of fluid between said lower substrate end (130) and said lower cover layer end (230); In said arrangement, a second seal (510) is provided between said first substrate lateral end (140) and said first cover layer lateral end (240), thereby preventing leakage of fluid between said first substrate lateral end (140) and said first cover layer lateral end (240); In said arrangement, a third seal (520) is provided between said second substrate lateral end (150) and said second cover layer lateral end (250), thereby preventing leakage of fluid between said second substrate lateral end (150) and said second cover layer lateral end (250); The arrangement thus forms a container open on one side for receiving a fluid, and further comprising a hardenable adhesive (310) within the container; B) pivoting the substrate (100) and the cover layer (200) relative to one another such that the distance from the upper cover layer end (220) to the upper substrate end (120) decreases and the adhesive (310) moves toward the upper substrate end (120) and the upper cover layer end (220); C) Curing the adhesive (310) Including, A method according to claim 1, characterized in that in the arrangement according to A), a further polymer layer (400) having a tensile strength according to DIN EN ISO 527 of 30 MPa or more is present between the substrate (100) and the cover layer (200).
10. 10. The method of claim 9, wherein the temperature of the polymer layer (400) is less than or equal to 50°C during at least steps A), B), and C).
11. 11. The method according to claim 9 or 10, wherein after step C), no heating of the layered composite to a temperature of 100°C or higher is performed.
12. The method according to any one of claims 9 to 11, wherein at least at the beginning of the pivoting in step B), the adhesive (310) has a viscosity at 20°C according to DIN EN 12092 of less than or equal to 50000 mPas.
13. The method of any one of claims 9 to 12, wherein the polymer layer (400) comprises a polyester polymer, a thermoplastic polyurethane polymer, or a polycarbonate polymer.
14. The method according to any one of claims 9 to 13, wherein the polymer layer (400) is formed as a film without depressions, as a film with one or more depressions (31), as a woven fabric, or as a non-woven fabric.
15. The method according to any one of claims 9 to 14, wherein the polymer layer (400) may not be or is not post-crosslinked.